(untitled) (Andamios, Revista de Investigación Social, 2025)
This article reflects on community autonomies as a subject, principle, means, and ends in struggles for emancipation, focusing on the Latin American context. From a theoretical-critical perspective and based on a review of specialized literature, it examines the construction of subjects emerging from collective struggles and the dynamics of community resistance, particularly among Indigenous communities, against the State and capital. It argues that these autonomies not only resist and seek immediate survival, but also promote the profound transformation of political and economic relations, both concrete and symbolic. Conceptually, the article explores three dimensions: autonomy- as-community-principle, community-autonomy-as-form, and autonomy-as- community-praxis, the latter conceived as the realization of the emancipatory horizon that guides community struggles.